WATER CONSERVATION MOCK-UP AS LEARNING MEDIA PROSPECTIVE STUDENTS FOR TEACHERS OF ENGINEERING BUILDING FOR ENVIRONMENTAL EDUCATION FACILITIES - Nur Cahyo Susilo; Taufiq Lilo Adi S; Anis Rahmawati (Indonesian Journal Of Civil Engineering Education, 2017)
Public awareness of the environmental conditions should be improved. This must bedone, given the increasingly damaged environmental conditions caused by human activitiesitself, to cause global warming and climate change that is exacerbating the situation.Environmental education needs to be instilled early on to learners, in order to create the nextgeneration who care about the environment. Therefore, students of construction engineeringprofessors must also have knowledge of the environment, closely related to the developmentof environmental aspects. The outcomes of this research are the conservation of water ingreen house, booklet, and lesson plan.This research includes descriptive research using research and development (R & D)level 1 method proposed by Sugiyono. The development model used is a descriptiveprocedural development model by following the research steps to produce a product. Thesteps of development in this research include: (1) preliminary study stage and design whichincludes three activities namely; (a) potentials and problems, (b) study of literature andinformation collection, and (c) product design; (2) development stage that includes maketmaking and design validation activities, (3) evaluation phase that is covering activityimprovement of product which developed to become a decent design. Sources of data in thisstudy are academic observers of green building, practitioners GBCI, environmental experts,learning experts, and media experts. Data obtained from the results of the study wereanalyzed quantitatively and qualitatively. The results of questionnaires from learning expertsand media experts were analyzed quantitatively, while interviews, documentation, andobservations to green building observers, GBCI practitioners, and environmental expertswere analyzed qualitatively.Based on the results of the study, obtained the validation results of expert learning, itcan be concluded that from the aspect of RPP, get a value of 91.67%. The study expertevaluates the RPP with very decent category. Then the results of validation of media experts,it can be concluded that from the aspect of learning media, get the value of 79%. The learningexpert assesses the learning medium with very decent category. The resulting product is amodel of water conservation in environmentally friendly house, booklet booklet, and learningimplementation plan (RPP) as guidance of media usage in learning. Based on the analysis ofdata and discussion can be concluded that the product is very feasible to be used as a mediumof learning for prospective students of building engineering teachers for environmentaleducation.Keyword: conservation, water conservation, media, learning media